Radical Gastrectomy: Still the Gold Standard Treatment for Gastric Cancer—Our Experience from a Tertiary Care Center from Northeast India - Purkayastha, Joydeep (Indian J Surg Oncol, 2019)
Gastric cancer (GC) is common in the northeast and southern parts of India. Radical surgery is the cornerstone of treatment and offers the only chance for cure. This study was conducted to assess the outcomes of all resectable gastric cancers that presented to our tertiary cancer center in Northeast India. All patients undergoing upfront surgery for gastric cancer with curative intention between 2012 and 2017 were included in the study. A total of 116 patients who underwent upfront radical gastrectomy were included in the study. Males (58.6%) were more common than females (41.4%). Mean age at presentation was 56.12 years (range 26–89). The most common mode of presentation was pain abdomen (53.8%). The most common location of tumor was the distal part (81%) followed by the proximal part (10.3%). The most commonly done procedure was distal radical gastrectomy (56.9%) followed by subtotal gastrectomy (32.8%). Median number of lymph nodes isolated was 14. Fifty-four patients received adjuvant chemotherapy while 32 patients received adjuvant chemoradiation (CTRT). At a median follow-up of 14 months (range, 2–78 months), overall 5-year survival was 23.75% (mean survival 33.77 months, median survival 24 months). The 5-year survival for stages I–III was 100%, 26.25%, and 11.25%, respectively (P < 0.001). Though perioperative chemotherapy has a role in gastric cancer, it is not the substitute for radical D2 gastrectomy which is still the gold standard treatment especially in high-volume centers.